Learning Innovation Through E-Worksheet Ethnomathematics: Improving Creative Thinking Skills - Hambali, Hambali; Mananay, Janet; Arkew, Habtu Worku (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
This study aims to develop ethnomathematics-based e-worksheets and analyze their effects on students' creative thinking skills in learning quadrilaterals and triangles. Ethnomathematics was chosen as an innovative approach that connects mathematical concepts with local wisdom, thus creating a more contextual and meaningful learning experience. E-worksheets are made with the stages of development, implementation, and evaluation adopted from branches using 90 samples from purposive sampling techniques. The data collection instrument was an essay test to measure students' creative thinking skills. Data analysis used an independent sample t-test statistical test with the help of SPSS 25 software. The study showed that the t-count value (14.216) was more significant than the t table (1.990) at a significance level of 0.05, indicating an essential difference between the experimental and control groups. The experimental group showed an average increase in creative thinking skills of 67.5%, much higher than the control group of 46.5%. This improvement is especially seen in originality and elaboration, which shows that ethnomathematics can stimulate students' creative ideas through relevant cultural contexts. This study offers a new approach to learning mathematics in the digital era through integrating local culture in e-worksheets, creating interactive learning media, and strengthening students' cultural identity. Using ethnomathematics-based e-worksheets is recommended as an alternative innovative and effective learning media to improve the quality of education, especially in building students’ creative thinking skills in the digital era.